2002
DOI: 10.1034/j.1600-0897.2002.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of IgG Purified from Women with SLE and Associated Pregnancy Loss on Rat Embryos in Culture

Abstract: Various antiphospholipid antibodies affect differently the growth and development of the embryo and the placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…34,35 It is interesting to note that the current maternal proteomic study revealed elevated production of IGG in BN dams. Increases in maternal IL6 and TNFɑ levels have been shown in women with pre-eclampsia, pro-inflammatory markers that are also upregulated in BN dams.…”
Section: Ically-determined Immune Phenotypes With Non-pregnant Bn Ratsmentioning
confidence: 81%
See 2 more Smart Citations
“…34,35 It is interesting to note that the current maternal proteomic study revealed elevated production of IGG in BN dams. Increases in maternal IL6 and TNFɑ levels have been shown in women with pre-eclampsia, pro-inflammatory markers that are also upregulated in BN dams.…”
Section: Ically-determined Immune Phenotypes With Non-pregnant Bn Ratsmentioning
confidence: 81%
“…Women with Th2-mediated inflammatory diseases such as systemic lupus erythematosus have higher frequency of pre-eclampsia and recurrent miscarriage in association with autoantibody production. 34,35 It is interesting to note that the current maternal proteomic study revealed elevated production of IGG in BN dams. Future assays will reveal whether BN dams produce antibodies that impair fetal growth or placental development.…”
Section: Ically-determined Immune Phenotypes With Non-pregnant Bn Ratsmentioning
confidence: 81%
See 1 more Smart Citation
“…At present, we have no explanation for these findings. However, emerging experimental evidence suggests that autoantibodies are implicated in pregnancy loss 10 through several potential pathogenetic mechanisms that involve a) reduction of embryo and yolk sac growth 34 as well as of trophoblast proliferation; 35 b) increase in the rate of trophoblast apoptosis; 35 adverse actions on molecules important for embryo and placental development such as laminin-1 36 and elastin. 37 Therefore, on the basis of these findings, it could be hypothesized that if the detection of ANA in a significant proportion of women with RPL can be interpreted as the expression of some derangement in the immune response or status in these subjects, then the detection of additional types of autoantibodies could represent the expression of a more marked disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The embryos were cultured in Dulbecco's Modified Eagle's Medium (DMEM)/F12 and 20% fetal calf serum (Ornoy et al, 2003a) in the presence of IgG and specific aPLA purified from SLE/APS patients with RPL, which were added to the culture medium in the same concentrations as in the original sera (Matalon et al, 2002;Ornoy et al, 2003b). At that stage, many of the embryonic organs have already been formed; therefore, it is expected that the main effects (if any at all) will be on embryonic growth and viability (Matalon et al, 2002). Reduced embryonic crown rump length (ECRL) and yolk sac diameter were measured in the embryos exposed to whole IgG obtained from patients with SLE/APS and RPL, in comparison to embryos that were exposed to IgG purified from healthy women or to embryos cultured in media without IgG.…”
Section: Rat Embryos and Human Placental Explants: Useful Culture Sysmentioning
confidence: 99%